The impacts of special environmental events on short-run electricity-saving behaviors. (2nd September 2021) - Shen, Xingchi; Qiu, Yueming; Luo, Ling; Zheng, Xiaohao
Abstract: Policymakers and academics are increasingly interested in using 'social nudges' to influence behavior, which are typically inexpensive relative to price-based and mandatory approaches. This study provides rigorous empirical evidence of the impacts of three big special environmental events, as a specific form of nudge, on short-run electricity-saving behaviors using high-frequency smart meter data in Shanghai, China, for both residential and commercial consumers. We find that World Environment Day and National Energy Saving Publicity Week caused commercial users to reduce their electricity consumption by 1.35 kWh h −1 and 0.6 kWh h −1 intra-event, around 17% and 8% reduction compared to average consumption, but the impacts decayed rapidly once the events ended. Earth Hour did not lead to significant energy-saving effects for both residential and commercial users. We further examine detailed activities implemented during these events to understand the heterogeneous impacts using social media and policy documents data.